PENERAPAN ETIKA BISNIS ISLAM DALAM TRANSAKSI JUAL BELI DI PASAR TRADISIONAL (STUDI PADA PT BANGUN PRIMA LESTARI KENCANA BEKASI) - Muhammad Nur Ishak; Robiatul Adawia (DIRHAM Jurnal Ekonomi Islam, 2022)
Islam is a complete and integrated system and way of life. He provides guidance on all aspects of life, including the commerce or sales sector. The purpose of this study is to find out how the understanding of Islamic business ethics among new market traders in Bekasi and how to apply Islamic business ethics among new market traders in Bekasi. The type of research conducted by the author is field research, namely research that is directly related to the object under study. The method used in this study is a qualitative descriptive method. The number of samples of traders in the new market in the new market of Bekasi is 20 respondents. The results of this study are based on the facts obtained from new market traders, about 17 people or 85% understand business ethics in trading, 2 people or 10% do not understand it, 1 person or 5% who do not understand Islamic business ethics in trading. Therefore, it can be concluded that a trader must apply the principles of Islamic business ethics in trading as well as position himself as a trader who applies honesty in order to become a businessman who adheres to Islamic business ethics.